2007
DOI: 10.1038/nature05471
|View full text |Cite
|
Sign up to set email alerts
|

An arid-adapted middle Pleistocene vertebrate fauna from south-central Australia

Abstract: How well the ecology, zoogeography and evolution of modern biotas is understood depends substantially on knowledge of the Pleistocene. Australia has one of the most distinctive, but least understood, Pleistocene faunas. Records from the western half of the continent are especially rare. Here we report on a diverse and exceptionally well preserved middle Pleistocene vertebrate assemblage from caves beneath the arid, treeless Nullarbor plain of south-central Australia. Many taxa are represented by whole skeleton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
119
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 16 publications
4
119
0
Order By: Relevance
“…Landscape burning by humans, who arrived in Australia approximately 50 kyr ago, has been advocated as a more likely explanation than hunting or aridity for the late Pleistocene extinction of Australia's megafauna by means of replacement of nutritious fire-sensitive plants with nutrient-poor, fire-adapted shrub/ grassland mosaics (3,4,27). In the case of P. goliah, however, a major component of its diet (chenopods including a large proportion of Atriplex) was less affected due to its relatively lower flammability (20,24,28,33).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Landscape burning by humans, who arrived in Australia approximately 50 kyr ago, has been advocated as a more likely explanation than hunting or aridity for the late Pleistocene extinction of Australia's megafauna by means of replacement of nutritious fire-sensitive plants with nutrient-poor, fire-adapted shrub/ grassland mosaics (3,4,27). In the case of P. goliah, however, a major component of its diet (chenopods including a large proportion of Atriplex) was less affected due to its relatively lower flammability (20,24,28,33).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that most species were gone by approximately 45,000 years (kyr) ago (2-3), leaving over-hunting (1,2), landscape burning (3,4) by humans after their arrival approximately 50 kyr ago, and/or increased aridity since the penultimate glacial maximum (6) as the 3 most strongly championed hypotheses. Most arguments are fuelled by the same 3 problems: paucity of well-dated occurrences and knowledge of prehuman faunal change, difficulties distinguishing ''absence of evidence'' from ''evidence of absence,'' and inadequate understanding of the ecologies of extinct taxa.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Precise location data for the site are registered with the Department of Earth and Planetary Sciences, Western Australian Museum, Perth. Fine-grained sediments in unit 3 are of reversed magnetic polarity, which along with overall species composition of the assemblage, indicate an early Pleistocene age (Matuyama Reversed Chron) (Prideaux et al, 2007). This falls within the Naracoortean land mammal age (Megirian et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…High species diversity and remarkably complete preservation are hallmarks of the assemblage, which fills a significant gap in our understanding of the Quaternary biogeography of southern Australia (Prideaux et al, 2007). Leaena 's Breath Cave is the only known Australian vertebrate locality that spans the early to middle Pleistocene boundary.…”
Section: Introductionmentioning
confidence: 99%